Numerical Analysis of a Tunnel Passing through Jointed Rockmass - Verma, Harshal; Ray, Arunava; Rai, Rajesh; Manna, Bappaditya; Singh, T. N. (Journal of the Geological Society of India, 2023)
With the increase in the pace of development, the demand for tunnels has increased in recent years. Analysing the stability of a tunnel in a fractured rock mass is a very challenging and cumbersome activity. The tunnel stability depends on the strength of the rock, joints bolt strength, in-situ stresses, and their orientation. This paper focuses on constructing tunnels in fractured/jointed rock mass. Three different software namely Rocscience Phase2 (finite element based), FLAC 3D (finite volume based) and PFC 3D (distinct element based), were used to analyse the performance and stability under static and dynamic loading conditions. The geomaterial properties used for the analysis were taken from data obtained after laboratory testing and based on available literature. The effect of joint orientation and bolt length was analysed using Phase 2 assuming plain strain conditions. The effect of earthquake and performance of fully grouted, energy absorbing and deformation-controlled bolts under seismic loading conditions were compared using FLAC 3D . While the 3D distinct element analysis of geometry was performed using PFC 3D to evaluate the effect of joints and their orientation. The performance of the different types of bolts was also analysed numerically. The behaviour of bolts can be customised using the ‘fish‘ function. The results indicate that analysis must incorporate the fusion of various numerical simulation techniques like finite element-, finite volume- and distinct element-based methods for more reliable results.